Towards a more equitable social organization of care: analysis of the design of five care systems in Latin America - Michel, Cynthia; Cejudo, Guillermo M.; Oseguera Gamba, Adriana S. (Revista del CLAD Reforma y Democracia, 2025)
Due to the ongoing care crisis in Latin America, in recent decades governments in the region have begun developing comprehensive care systems. This article offers a comparative analysis of five emblematic care system designs—three at the national level (Chile, Uruguay, and Costa Rica) and two at the subnational one (Bogotá, Colombia, and San Pedro Garza García, Mexico)—that explicitly aim to coordinate policy interventions for caregivers and care recipients. We examine these systems through a public policy lens. We argue that understanding how these systems reshape the social organization of care requires a comprehensive analysis of the policies involved, the interplay among their instruments—regulations, goods, and services—and their target populations. Drawing on literature reviews, official documents, and interviews, we identify the design components of each system. Taking as a reference the objectives of recognizing, reducing, and redistributing unpaid care work, along with ensuring the right to care, we explain how these systems contribute to a more equitable care structure.